The sensitivity of diphtheria bacilli to eight antibiotics - Zamiri, Iraj (1972)
Antibiotics are of equal importance to antitoxin in the treatment of diphtheria, as an effective antibiotic rapidly halts the production of toxin. There appear to have been only two reports of the sensitivity of diphtheria bacilli to various antibiotics and these are based on the examination of less than 60 strains. In this paper the sensitivity of 192 strains to eight representative antibiotics is reported.